Doing Business in Mexico - World Bank; International Finance Corporation (Washington, DC, 2013)
This report investigates the scope and manner of regulations that enhance business activity and those that constrain it. Quantitative indicators on business regulations and their enforcement have been created for 12 cities and states, which can now be compared with Mexico City, and to 154 countries around the world. The indicators cover four "Doing Business" topics: starting a business, registering property, getting credit and enforcing contracts. The 12 cities and states are: Aguascalientes, Aguascalientes; Celaya, Guanajuato; Ciudad Juárez, Chihuahua; Guadalajara, Jalisco; Merida, Yucatan; Monterrey, Nuevo Leon; Puebla, Puebla; Queretaro, Queretaro; San Luis Potosí, San Luis Potosi; Tlalnepantla, Estado de Mexico; Torreon, Coahuila; and Veracruz, Veracruz. Comparisons with Mexico City and other countries are based on the indicators in Doing Business in 2006 - Creating Jobs (see report no. 34550).